Identification of ca. 850 Ma high-temperature strongly peraluminous granitoids in southeastern Guizhou Province, South China: A result of early extension along the southern margin of the Yangtze Block - Wu, T.; Zhou, J.; Wang, Xuan-Ce; Li, W.; Wilde, Simon; Sun, H.; Wang, J.; Li, Zhen (Elsevier BV, 2018)
Strongly peraluminous granites are characterized by high A/CNK values (>1.1) and are important for understanding the regional tectonic regime. Here, we present integrated studies of zircon U–Pb ages, trace elements and Lu–Hf isotopes, whole-rock major and trace elements, and Nd isotope compositions for the newly discovered Nage granite porphyry in southeastern Guizhou Province. The porphyry has a crystallization age of 852 ± 5 Ma and shows wide ranges in SiO2 (64.5–72.51 wt%) and Al2O3 (13.08–19.34 wt%) contents, with low TiO2 (0.41–0.84 wt%) and P2O5 (<0.15 wt%) contents. All the samples are strongly peraluminous with A/CNK >1.1, and they have similar trace element patterns with depletion in high field strength elements (HFSE, e.g., Nb and Ta) and enrichment in large-ion lithophile elements (LILE, e.g., Rb, Th and U). Initial zircon Hf isotopes of the porphyry vary from εHf(t) = −7.6 to −0.6, whereas whole-rock Nd isotopes are relatively uniform with εNd(t) = −6.0 to −6.7. They record high zircon saturation temperatures (Tzr) (786–842 °C, mostly >810 °C), but low oxygen fugacity (log fO2 = −16 to −25, corresponding to ΔFMQ −3 to ΔFMQ −7) and emplacement pressure of <0.5 GPa. Major and trace elements, 10,000 Ga/Al ratios and Zr + Nb + Ce + Y values, show good correlations with Tzr, indicating that fractional crystallization may have played an important role. Although these granites show low P2O5 contents that decrease with increasing Rb, the high A/CNK (>1.1), K2O/Na2O (0.7–2.6; average 1.4) and CaO/Na2O (0.2–0.8; mostly >0.5) ratios suggest that clay-poor metasedimentary rock were dominant in the source. Combined with the Nd–Hf isotopes, we suggest that the Nage granite porphyry formed by anatexis of an immature arkose and greywacke source, which was a mixture of weathered juvenile igneous materials and minor recycled ancient crustal components. The ca. 850 Ma strongly peraluminous granites, along with coeval extension-related magmatism along the southwestern margin of the Yangtze Block, indicate an extensional environment started as early as ca. 850 Ma.